Evaluation of toxicity and antioxidative effects of Tussilago farfara and Verbascum thapsus water extracts in zebrafish and in bronchial epithelial cells - Dragičević, Sandra; Kovačević, Draginja; Divac Rankov, Aleksandra; Nikolić, Aleksandra; Radojković, Dragica; Radović, Svetlana (Archives of Biological Sciences, 2019)
Paper description: T. farfara and V. thapsus have long been used as natural supplements for treating respiratory disorders. This is the first study to investigate the toxicity of T. farfara and V. thapsus extracts in zebrafish and their anti-oxidative properties in cell culture. V. thapsus extract showed toxic effects on zebrafish embryos and BEAS 2B epithelial bronchial cells. T. farfara extract exerted a protective effect on the cells after induction of oxidative stress. Our findings further elucidate the function of T. farfara as a natural medicine for treating respiratory disorders through its potential anti-oxidative effects on epithelial bronchial cells. Abstract: Tussilago farfara (coltsfoot) and Verbascum thapsus (mullein) have been used as folk remedies for treating respiratory disorders. The aim of this study was to test the toxicity of the water extracts of T. farfara and V. thapsus in vivo in zebrafish and in vitro in BEAS 2B epithelial bronchial cells. To the best of our knowledge, this is the first study to investigate the antioxidative properties of T. farfara and V. thapsus extracts in cell culture. Our results show that the T. farfara leaf extract does not produce toxic effects on zebrafish embryos or BEAS 2B cells, and that it has a protective effect in BEAS 2B after induction of oxidative stress. The water extract from V. thapsus displayed pronounced toxic effects on zebrafish embryos and BEAS 2B cells and did not exhibit a significant antioxidative effect on BEAS 2B cells exposed to oxidative stress. Our results suggest that the use of T. farfara water leaf extract is potentially safe and effective in treating respiratory disorders, whereas the use of V. thapsus needs further investigation. https://doi.org/10.2298/ABS181213022D Received: December 13, 2018; Revised: March 1, 2019; Accepted: March 26, 2019; Published online: April 4, 2019 How to cite this article: Dragičević S, Kovačević D, Divac Rankov A, Nikolić A, Radojković D, Radović S. Evaluation of toxicity and antioxidative effects of Tussilago farfara and Verbascum thapsus water extracts in zebrafish and in bronchial epithelial cells. Arch Biol Sci. 2019;71(3):409-16.